Environmental factors differentially affect epistaxis among preschool and school-aged children - Ahn, Eun-Jin; Min, Hyun Jin (Frontiers in Public Health, 2023)
Introduction: Environmental factors are closely associated with pediatric epistaxis. Whether this association differs according to age has not been previously reported. Therefore, we tried to evaluate the differences in associations between environmental factors and epistaxis in children of different ages.Methods: A total of 20234 patients with epistaxis who visited the hospital between January 1, 2002, and December 31, 2015, were enrolled in this study. The patients were divided into two groups according to their ages: preschool-aged (< 6 years) and school-aged children (6-18 years). Daily, monthly, and yearly data on environmental factors were collected. We performed a stepwise logistic regression to identify the potential environmental risk factors for epistaxis in each age group.The mean number of epistaxis cases per month in both groups was highest in September. The cases were lowest in February in preschool-aged children and in November in school-aged children. Temperature, humidity, maximum wind speed, and sunshine duration were associated with epistaxis in preschool-aged children. Average wind speed, particulate matter (> 10 µm diameter), temperature, humidity, sunshine duration, and sulfur dioxide concentration were associated with epistaxis in school-aged children.This study indicates that the differences in environmental risk factors for epistaxis are associated with the patient's age.